Atopy and acquired immune deficiency - issues of control of two extremes of a spectrum of paediatric respiratory disorders with an immunological basis - Van Heerden, Willem Francois Petrus (University of Pretoria, 2014)
Thesis (DSc)--University of Pretoria, 2013.